Cost Analysis of Community-Based Violence Prevention Programs: Manhood 2.0 and Job Skills Programs - Tang, Shichao (Journal of family violence, 2024)
Purpose: Sexual violence (SV) and adolescent relationship abuse (ARA) are common in the U. S. and have strong associations with negative health and wellbeing outcomes. Manhood 2.0 is the first U.S. program designed for community settings to build bystander skills while also challenging harmful gender norms. A cluster-randomized trial comparing Manhood 2.0 to Job Skills, a job readiness training control condition, demonstrated that it is a promising strategy to prevent sexual violence and adolescent relationship abuse. Such community-based interventions may be particularly relevant in lower resource urban settings, and the costs of such prevention programs have not been considered previously. Methods: The aim of the present study is to perform systematic and standardized cost calculations associated with implementing Manhood 2.0 among adolescent males. In addition, this study provides detailed cost information of the community-based intervention program, as well as costs associated with implementing the Job Skills control program. Program implementation data were recorded throughout the study period (2015–2019) by the Manhood 2.0 study team. Results: The cost of implementing Manhood 2.0 is USD4,771 per complete round of program delivery and USD451 per participant, which is approximately the same cost as the control Job Skills program (USD4,432 and USD453 per participant). The marginal cost per additional round of Manhood 2.0 program is USD3,682. Conclusion: Implementation of a community-based program requires substantial resources and collaborations with community partners especially in economically disadvantaged neighborhoods. This study provides a snapshot of the cost information of a community-based intervention program from the implementing agency’s perspective, which is essential in helping decision-makers understand the costs they will incur by implementing prevention programs and ensuring program feasibility and sustainability.